Unemployment Persistence in The Turkish Labor Market - Selçuk Gemicioğlu; Hasan Şahin (İktisat Politikası Araştırmaları Dergisi)
The aim of this study is to investigate the existence of unemployment persistence in the Turkish labor market. In this regard, the existence and degree of genuine state dependence was analyzed using the data obtained from the 2013-2016 Survey on Income and Living Conditions and Household Labor Force Survey. The dynamic random effects probit model estimation results showed that there is genuine state dependence in the Turkish labor market. In other words, after controlling for observed and unobserved heterogeneity and initial conditions, past unemployment experiences increased the probability of being unemployed in the future. In addition, the marginal effect of genuine state dependence was found to be higher for the unemployed individuals than for the individuals employed in the initial period. As one’s education level increases, the likelihood of being jobless declines, however, men are more likely than women to do so. Age, gender, education level, marital status, and the number of household employees all have an impact on the likelihood of being unemployed. Demand-side factors such as the unemployment rate and growth rate of employment do not affect the probability of remaining unemployed.